GAGASAN PENERAPAN SANKSI TINDAKAN TERHADAP ANAK PELAKU PROSTITUSI DALAM PEMBAHARUAN HUKUM PIDANA DI INDONESIA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Indonesia is currently not only facing the dangers of prostitution perpetrated by adults, but also child prostitution. The practice of prostitution of minors is very concerning. General regulations that have been enacted in the Criminal Code, which are nationally binding, but cannot provide clear sanctions for prostitution of minors. Furthermore, the aims of this research are: first, to find out the reasons for the need to apply action sanctions against child prostitutes in the renewal of criminal law in Indonesia. Second, to find out the ideal idea in the application of sanctions applied to child prostitutes.Moreover, this law study is using normative legal research. An approach that is used for this study is normative juridical approach. Also, this study use qualitative data for finding the justification. Later on, to get the conclusion the researcher uses deductive thinking method where getting the conclusion by adopting statements or law of general nature to be specific statements.Lastly, the importance of actions sanctioning against child prostitutes to provide comprehensive protection of children's rights, with criminal law reform, is expected to provide clear arrangements in the future, especially regarding prostitution carried out by minors, namely related to the criminalization of the practice of prostitution. The ideal idea in implementing sanctions against child prostitutes by providing action sanctions against child prostitution is an effective step to conquer child prostitution. Key Words: Idea – Child Prostitution – Actions Sanctioning – Criminal Law Reform